A taxonomic review of freshwater fishes in Eastern Ghats, India (Zoological Records and Reviews, 2021)
The Eastern Ghats of India represent one of the most ecologically significant and underexplored freshwater ichthyofaunalzones in the Asian subcontinent. Stretching discontinuously along the eastern coast from Odisha through AndhraPradesh to Tamil Nadu, this ancient hill system drains into multiple river basins including the Mahanadi, Godavari,Krishna, and Cauvery, each harbouring distinct fish assemblages shaped by geological isolation, seasonal monsoondynamics, and varying altitude gradients. Despite their biogeographic significance, the freshwater fishes of the EasternGhats remain taxonomically incomplete, with numerous species either inadequately described, synonymised withoutrigorous justification, or entirely undocumented. This review synthesises taxonomic records from museum collections,published literature spanning 1822 to 2021, and original field surveys conducted across fourteen river systems. Wedocument 312 valid freshwater fish species belonging to 94 genera and 38 families, including 47 endemic species, 11species newly recorded from the region, and 6 candidate species requiring formal description. The family Cyprinidaesensu lato dominates the fauna with 118 species, followed by Balitoridae with 34 species and Gobiidae with 28 species.Phylogenetic analysis of selected endemic cyprinids using mitochondrial COI and 16S rRNA markers confirms thedistinctiveness of Eastern Ghats lineages from Western Ghats and Gangetic plain congeners. Updated dichotomouskeys, morphometric tables, and distribution maps are provided for all documented taxa. Fourteen species are assessedas Critically Endangered under IUCN criteria. Conservation recommendations and priorities for future taxonomic work are discussed.